A Single Amino Acid Change in Rabies Virus Glycoprotein Increases Virus Spread and Enhances Virus Pathogenicity - Faber, Milosz (American Society for Microbiology, 2005)
Several rabies virus (RV) vaccine strains containing an aspartic acid (Asp) or glutamic acid (Glu) instead of an arginine (Arg) at position 333 of the RV glycoprotein (G) are apathogenic for immunocompetent mice even after intracranial inoculation. However, we previously showed that the nonpathogenic phenotype of the highly attenuated RV strain SPBNGA, which contains a Glu at position 333 of G, is unstable when this virus is passaged in newborn mice. While the Glu(333) remained unchanged after five mouse passages, an Asn(194)→Lys(194) mutation occurred in RV G. This mutation was associated with increased pathogenicity for adult mice. Using site-directed mutagenesis to exchange Asn(194) with Lys(194) in the G protein of SPBNGA, resulting in SPBNGA-K, we show here that this mutation is solely responsible for the increase in pathogenicity and that the Asn(194)→Lys(194) mutation does not arise when Asn(194) is exchanged with Ser(194) (SPBNGA-S). Our data presented indicate that the increased pathogenicity of SPBNGA-K is due to increased viral spread in vivo and in vitro, faster internalization of the pathogenic virus into cells, and a shift in the pH threshold for membrane fusion. These results are consistent with the notion that the RV G protein is a major contributor to RV pathogenesis and that the more pathogenic RVs escape the host responses by a faster spread than that of less pathogenic RVs.